Contemporary management of Hirschsprung disease in New Zealand. Issue 6 (2nd June 2020) - Taghavi, Kiarash; Goddard, Lucy; Evans, Stephen M.; Hobson, Andrew; Beasley, Spencer W.; Sankaran, Sasikumar; Kukkady, Askar; Stevenson, Jonathan; Stringer, Mark D.
Abstract: Background: The aim of this study was to report the contemporary management of Hirschsprung disease (HD) in New Zealand. Methods: We undertook a national multi‐centre retrospective review of all newly diagnosed cases of HD during a 16‐year period (2000–2015). Demographics, genetic and syndromic associations, family history, radiology and histology results and surgical interventions were analysed. Results: A total of 246 cases (males:females 4:1) were identified, an incidence of 1:3870 live births. Short‐segment disease was present in 81.7%, long‐segment disease in 8.5%, total colonic aganglionosis in 6.5% and unknown in 3.3%. HD was diagnosed by 4 weeks' corrected gestational age in 67%. Thirty cases (12%) also had Trisomy 21. Fifty‐three (21.5%) patients required a repeat rectal biopsy for definitive diagnosis. A contrast enema was performed in 55% and identified the transition zone with 69% accuracy. Primary pull‐through surgery was undertaken in 59% (65% of short‐segment cases) at a median age of 27 days; others were initially managed by a defunctioning stoma. The commonest definitive procedure was a Soave‐Boley endorectal pull‐through (79%) (or similar variant). During a median follow‐up of 7.4 years, six (2.5%) survivors underwent a redo pull‐through, 13 (5.5%) an appendicostomy, 16 (6.8%) a defunctioning stoma and 10 never had a definitive procedure. Total colonic aganglionosis was significantly more likely to be fatal (12.5% versus 0.5%, P < 0.0005) or associated with a permanent end stoma (27.5% versus 4.5%, P < 0.0005). Conclusions: Most New Zealand born infants with short‐segment HD are currently managed by primary pull‐through, usually in the first months of life. Abstract : This study of a complete national cohort of children diagnosed with Hirschsprung disease (HD) and followed for a median of more than 7 years highlights the contemporary management of HD. Most New Zealand born infants with short‐segment HD are currently managed by primary pull‐through, usually in the first months of life.